Plasmodium falciparum genetic variation of var2csa in the Democratic Republic of the Congo - Verity,RJ; Hathaway,N; Waltmann,A; Doctor,S; Watson,O; Patel,J; Mwandagalirwa,K; Tshefu,A; Bailey,J; Ghani,A; Juliano,J; Meshnick,S (Malaria Journal, 2018)
Background: The Democratic Republic of the Congo (DRC) bears a high burden of malaria, which is exacerbated inpregnant women. The VAR2CSA protein plays a crucial role in pregnancy-associated malaria (PAM), and hence quantifyingdiversity at the var2csa locus in the DRC is important in understanding the basic epidemiology of PAM, and indeveloping a robust vaccine against PAM.Methods: Samples were taken from the 2013–14 Demographic and Health Survey conducted in the DRC, focusingon children under 5 years of age. A short subregion of the var2csa gene was sequenced in 115 spatial clusters, givingcountry-wide estimates of sequence polymorphism and spatial population structure.Results: Results indicate that var2csa is highly polymorphic, and that diversity is being maintained through balancingselection, however, there is no clear signal of phylogenetic or geographic structure to this diversity. Linear modellingdemonstrates that the number of var2csa variants in a cluster correlates directly with cluster prevalence, but not withother epidemiological factors such as urbanicity.Conclusions: Results suggest that the DRC fts within the global pattern of high var2csa diversity and little geneticdiferentiation between regions. A broad multivalent VAR2CSA vaccine candidate could beneft from targeting stableregions and common variants to address the substantial genetic diversity.